Joint maintenance planning of deteriorating co-located road and water infrastructures with interdependencies. (October 2022) - Nguyen, Hung; Abdel-Mottaleb, Noha; Uddin, Shihab; Zhang, Qiong; Lu, Qing; Zhang, He; Li, Mingyang
Abstract: Due to co-location and spatial proximity, deteriorating water infrastructure (WI) and transportation infrastructure (TI) have complex interdependencies, including both physical dependency from road to pipe, and operational dependency from pipe to road. On one hand, traffic load is not only a dominant factor for the physical degradation of road but may also be an important contributing factor to the sudden failure of the pipe underneath the co-located road due to the extreme propagated stress. On the other hand, the water pipe breaks and repairs will also cause traffic blockage, lane closure, and repaving of road surface, which influence both road user costs and road maintenance costs. Most of the existing maintenance work mainly considered WI and TI separately but neglected their complex interdependencies. This study proposes a joint proactive maintenance planning framework for the co-located road and pipe under their degradation uncertainties by explicitly taking into account both their physical and operational dependencies. In particular, the competing failure modes of both the traffic-induced sudden failure and the corrosion-induced gradual failure are simultaneously considered for the pipe to capture the physical dependency. Road maintenance costs and road user costs in the presence of pipe maintenance disruption are also formulated for the road to capture the operational dependency. A case study is further provided to comprehensively evaluate the performance of the proposed joint maintenance planning strategy over several existing benchmark strategies and demonstrate the cost-saving benefit of the proposed work. The impacts of interdependencies on the proposed maintenance planning decisions are also thoroughly investigated. Highlights: Developing a cost-effective maintenance planning model under degradation uncertainty for the co-located road and pipe with interdependencies. Considering both physical and operational dependencies between the co-located road and pipe. Characterizing multiple competing failure modes of the pipe. Considering both the short-term and long-term users' costs for determining optimal maintenance decisions.